Program CSR PT Astra Internasional Dalam Upaya Pengelolaan Lingkungan Hidup melalui Gerakan Semangat Kurangi Plastik - qonaah, siti qonaah; Giantika, Gan Gan; Bender, George Wilhelm (LPPM Universitas Bina Sarana Informatika, 2022)
ABSTRACT Improper waste management has a negative impact on the health of the surrounding community. The Department of Environment and Hygiene (DLHK) of Tangerang Regency, Banten, noted that the volume of waste reached 2,250 tons per day so that the total for one year in 2021, waste production reached around 820,000 tons. PT Astra Internasional carries out social responsibility in environmental management with the Movement to Reduce Plastic Spirit program. The purpose of this study is to describe Astra International's CSR Program in Environmental Management Efforts through the Passion to Reduce Plastics Movement in Kampung Berseri Astra Talagasari, Balaraja, Tangerang. The research methodology uses a qualitative methodology with a case study method. Methods of data collection through literature study and observation. The results showed that the Astra International CSR Program in Environmental Management Efforts through the Movement to Reduce Plastic Spirit in the Kampung Berseri AstraTalagasari, Balaraja succeeded in reducing plastic waste by around 844 kg per month or 10.2 tons. Waste management carried out by Kampung Berseri Astra Talagasari through a waste bank with 3Rs, namely reduce, reuse, and recycle. With the Corporate Social Responsibility Program, the spirit of reducing waste has fulfilled the concept of Corporate Social Responsibility, namely people, planet, profit. Thus PT Astra has paid attention to the welfare of the community both in terms of a clean environment and also improving the economy of the people of Kampung Berseri Astra Talagasari Tangerang Banten. Keyword: Corporate Social Responsibility, Environmental Management